Structure and function of cholera toxin and the related Escherichia coli heat-labile enterotoxin. - Spangler, B D (1992)
Cholera and the related Escherichia coli-associated diarrheal disease are important problems confronting Third World nations and any area where water supplies can become contaminated. The disease is extremely debilitating and may be fatal in the absence of treatment. Symptoms are caused by the action of cholera toxin, secreted by the bacterium Vibrio cholerae, or by a closely related heat-labile enterotoxin, produced by Escherichia coli, that causes a milder, more common traveler's diarrhea. Both toxins bind receptors in intestinal epithelial cells and insert an enzymatic subunit that modifies a G protein associated with the adenylate cyclase complex. The consequent stimulated production of cyclic AMP, or other factors such as increased synthesis of prostaglandins by intoxicated cells, initiates a metabolic cascade that results in the excessive secretion of fluid and electrolytes characteristic of the disease. The toxins have a very high degree of structural and functional homology and may be evolutionarily related. Several effective new vaccine formulations have been developed and tested, and a growing family of endogenous cofactors is being discovered in eukaryotic cells. The recent elucidation of the three-dimensional structure of the heat-labile enterotoxin has provided an opportunity to examine and compare the correlations between structure and function of the two toxins. This information may improve our understanding of the disease process itself, as well as illuminate the role of the toxin in studies of signal transduction and G-protein function.